2019
DOI: 10.4251/wjgo.v11.i9.686
|View full text |Cite
|
Sign up to set email alerts
|

Tumor progression-dependent angiogenesis in gastric cancer and its potential application

Abstract: Despite improvements in the early diagnosis, prognosis and therapeutic strategies for gastric cancer (GC), human GC remains one of the most frequently diagnosed malignant tumors in the world, and the survival rate of GC patients remains very poor. Thus, a suitable therapeutic strategy for GC is important for prolonging survival. Both tumor cells themselves and the tumor microenvironment play an important role in tumorigenesis, including angiogenesis, inflammation, immunosuppression and metastasis. Importantly,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 155 publications
0
31
0
3
Order By: Relevance
“…One different anti-angiogenic strategy encompasses therapies targeting the angiogenic VEGF-mediated pathway, which is considered critical not only for the regulation of tumor angiogenesis but also for the degradation and remodeling of the ECM [191]. Significant evidence awards VEGF/VEGFR2 signaling an important role in gastric cancer pathogenesis, and indeed, gastric cancer patients were reported to display significantly higher plasma or serum VEGF levels than healthy control subjects [192]. The monoclonal anti-VEGF antibody Bevacizumab, which was the first drug targeting the VEGF pathway, did not reach promising results in overall survival of gastric cancer patients in the AVAGAST clinical trial, however, it is now approved for first-and/or second-line treatment of a variety of tumors including colorectal cancer [191].…”
Section: Potential Therapeutic Targets and Strategiesmentioning
confidence: 99%
“…One different anti-angiogenic strategy encompasses therapies targeting the angiogenic VEGF-mediated pathway, which is considered critical not only for the regulation of tumor angiogenesis but also for the degradation and remodeling of the ECM [191]. Significant evidence awards VEGF/VEGFR2 signaling an important role in gastric cancer pathogenesis, and indeed, gastric cancer patients were reported to display significantly higher plasma or serum VEGF levels than healthy control subjects [192]. The monoclonal anti-VEGF antibody Bevacizumab, which was the first drug targeting the VEGF pathway, did not reach promising results in overall survival of gastric cancer patients in the AVAGAST clinical trial, however, it is now approved for first-and/or second-line treatment of a variety of tumors including colorectal cancer [191].…”
Section: Potential Therapeutic Targets and Strategiesmentioning
confidence: 99%
“…Substantial evidence suggests that angiogenesis is involved in processes of carcinogenesis, progression, and metastasis of GC. Moreover, results from translational research on angiogenesis in GC indicate that several angiogenesis-related factors might be prognostically relevant [ 9 , 15 , 16 , 17 ]. Although analyzing the expression levels of a single angiogenetic gene is convenient with immunohistochemistry and ELISA [ 17 , 18 ], multiple gene signature analysis reflects the complex interaction of various parameters affecting angiogenesis in tumor pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Angiogenesis is an essential process in tumorigenesis, because its induction is indispensable to deliver nutrients and evacuate metabolic waste [ 8 ]. During cancer development, several proangiogenic cytokines are released by tumor cells, such as vascular endothelial growth factor A (VEGFA), fibroblast growth factor (FGF) and hypoxia-inducible factor-1 (HIF-1), which contributes to the sprout and formation of neovasculature in the tumor microenvironment (TME) [ 9 ]. Thus, it had been demonstrated that anti-angiogenic therapies significantly improved prognosis in GC patients [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The initiation and development of GC is a multi-stage, heterogeneous and multifactorial pathology process involving numerous genetic, epigenetic and environmental factors alterations [22]. Recently, studies have reported that the ATP4B gene is downregulated in GC, which plays a negative role in the progression of GC [6,15].…”
Section: Discussionmentioning
confidence: 99%